Smart against ageism: an overview of age discrimination in Portugal - Dantas, Carina; Louceiro, Juliana; Machado, Natália (Magyar Gerontológia, 2022)
Negative stereotypes, prejudices and discrimination on the ground of age, known as “ageism” have been shown to cause cardiovascular stress, lowered levels of self-efficacy and decreased productivity[1]. Across the EU, policies and practices still reflect ageist prejudices and deprioritise, disregard, or even exclude older adults in different ways.